Economic analysis of agricultural project - Gittinger, James Price (Published for the Economic Development Institute of the World Bank [by] Johns Hopkins University Press, 1982)
The book presents a sound, careful methodology for project analysis based on efforts of agricultural specialists... Care has been taken to make the technical topics discussed understandable to those without advanced training in economics